A Christian Theological Review on Character and Spiritual Transformation - Maruli Tua Tampubolon; Stefanus Dully (International Journal Labs, 2025)
Character and spiritual transformation aims to describe how the standard of life and character of each person is before and after accepting and placing God in his or her life. Professionals will have a professional character, while those who live in the social world live a life with the culture they accept and aim to live a life without involving God. Furthermore, those who are willing to accept God and become new creations will live as believers who serve God alone. This paper aims to explore how character and spiritual transformation occurs when individuals move from living according to cultural or professional ethics to adopting Christian values. This paper uses a qualitative descriptive method. Research shows that character and spiritual transformation only occurs when there is a transformation from character standards in the form of codes of ethics or culture to biblical standards. Successful transformation can only be assured by the presence of surrender and the helpful role of the Holy Spirit. The success of the transformation will bring about a change in the standard of character to the Christian character or the standard of Christ, prioritizing serving the Lord God and improving the spirituality and life of the believer.